Confinement fluorescence effect of an aggregation‐induced emission luminogen in crystalline polymer - Lan Zhou; Linlin Zheng; Xiaoxiao Yu; Mengyue Gao; Chengjian Xu; Yifan Ge; Tianxiang Bai; Jin Wen; Yanhua Cheng; Meifang Zhu (Aggregate, 2023)
Abstract Despite the impressive progress of stimuli‐responsive fluorescent materials, little is known about the influence of confinement created by crystalline polymer over the fluorescence properties of fluorescent molecules. The effects of confinement on the fluorescence of an aggregation‐induced emission luminogen (AIEgen) are investigated using computational simulations, which reveal that the confined space induces the AIEgens to take a more planar conformation, resulting in a red‐shifted emission spectrum. With this property, the study is extended to explore the confinement generated by various polymer crystalline forms, and it is shown that different fluorescence colors are activated. This confinement fluorescence effect is attributed to the different spatial dimensions of the polymer amorphous layer between lamellar crystals where the AIEgens are located. These results indicate the immediate association between crystalline structure and fluorescence signals, activating unprecedented photophysical properties of luminescent materials, and also providing the possibility for crystalline structure visualization, it is important for the many polymer crystallization processes occurring in the materials processing.